Social Stratification - Yi, Li (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Social stratification and social organization are the core of sociology. From the beginning of the history of social thought, stratification has remained an enduring center for social thinkers. This course discusses major forms of stratification in human society, examines the powerful models, methods, and concepts that serious scholars of stratification have deployed, and helps you understand your chances of moving up or down in the class order and the chances to be a member of a ruling class in America. Our individual goals, ambitions and experiences are shaped and oftentimes limited by structural forces. In reality, the "American Dream" really exists for only a few. We cannot truly understand our own society without some knowledge of others.